Perancangan UI/UX Sistem Informasi Pendaftaran dan Antrian Online Klinik K24 Menggunkan Metode Design Thinking - Muhammad Risman; Emy Lenora Tatuhey (CV Edujavare Publishing, 2025)
The rapid advancement of information technology has brought significant improvements in the efficiency of healthcare services, especially in patient registration systems. Klinik K24 Abepura currently relies on a manual system, leading to long queues, data entry errors, limited access to doctor schedules, and poor data security. This research aims to design an online registration and queue management system using a website platform with the Design Thinking approach, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. Observations and interviews were conducted to identify user needs. The resulting system allows patients to register online, view real-time doctor schedules, and receive queue notifications. A prototype was developed using Figma for three user roles: patients, doctor assistants, and administrators. Usability testing involving 10 respondents used the System Usability Scale (SUS), resulting in an average score of 81.5, categorized as “Excellent.” The system enhances administrative efficiency, reduces queues, and improves the overall user experience. Additionally, security measures such as encryption and user authentication ensure the protection of sensitive medical data. These findings suggest that the system is feasible and can serve as an adaptive digital solution to existing challenges in healthcare clinic services.